Commodity Channel Index: Evaluation of Trading Rule of Agricultural Commodities - Maitah, Mansoor; Procházka, Petr; Cermak, Michal; Å rédl, Karel (International Journal of Economics and Financial Issues, 2016)
This paper is focused on evaluating the trading rule of indicator Commodity Channel Index, using selected agricultural commodities. The reason of testing is that this indicator is calculated with respect to fluctuation of commodity market – volatility. The recent issue of commodity markets examines trading under risk. The concept is in analyzing of predictive power of Commodity Channel Index. The main core of this paper is if the trading strategy under evaluating using technical analysis, respectively Commodity Channel Index, reaches positive profit. The returns of trading rule are measured using signals to buying or selling and comparison each of them. Authors of this paper created trading rule based on Commodity channel index and tested it on commodity markets. The results are positive in term of % CCI. Findings of the strategy are positive due to measurement volatility involved in indicator. The commodity markets are volatile, time series are fluctuating due to actual announcements or news. Keywords: Commodity Channel Index, agricultural commodities, trading JEL Classifications: C22, C53, G17